(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper we put forward a system that bridges the gap between people who use Sign Language to communicate and the computer. Sign Language Recognition systems, though much crucial, suffer the lack of implementation in our common day to day devices. This paper focuses on various techniques and tools to help resolve this gap using Deep Learning. Here we propose a system that recognizes sign language and predicts the right sign using a web camera. The system uses Deep learning techniques, Convolution neural networks, max pooling and ReLU activation function. We aim to create a software which is both affordable, much more accessible to the users and works without compromising with the desired results.